ROLE OF SELF-TALK IN PREDICTING DEATH ANXIETY, OBSESSIVE COMPULSIVE DISORDER, AND COPING STRATEGIES IN THE FACE OF COVID-19 AMONG UNIVERSITY STUDENTS - Safdar, Iqra; Gulab, Ifat; Gul, Nighat (Pakistan Journal of Physiology, 2024)
Background: The current study examines, the role of self-talk in death anxiety, obsessive compulsive disorder (OCD), and coping strategies faced during COVID-19 by university students. The study was conducted among university students after COVID. Method: This study included 300 university students, living within the zones of Haripur, Pakistan. They participants were chosen using purposive sampling technique. The self-talk scale (STS), coping strategies inventory short form (CSISF), death anxiety scale (DAS), and Yale-Brown Obsessive-Compulsive Scale (YBOCS) were utilized for assessment. Information was analysed with Student’s t-test and simple linear regression. Results: The female students significantly scored higher on STS, DAS, and CSISF, while male students scored higher on YBOCS. The regression test indicated that self-talk was a significant predictor of coping strategies and death anxiety among university students. Conclusion: Self talk was the predictor of death anxiety, obsessive compulsive disorder and copying strategies during COVID-19 outbreak among students gender wise Pak J Physiol 2024;20(1):48-51